Parents’ Perceptions of the Physical Health Outcomes of Young People Diagnosed with First Episode Psychosis - Chee, G.L.; Wynaden, Dianne; Heslop, Karen (TAYLOR & FRANCIS INC, 2019)
This study explores parents’ perceptions of their son/daughter’s physical health needs following a first episode psychosis diagnosis and commencement on antipsychotic medication. The research process was guided by grounded theory methodology and data were collected using semi-structure interviews with 16 parents. Four categories were identified. Participants described the importance, challenges and strategies for their son/daughter to maintain their physical health, and the need to improve young people’s health literacy, particularly in areas of physical health, diet and lifestyle. These findings will assist health professionals to provide parents with information to better support their son/daughter to maintain their physical health.